Customers’ Perception and Encounters in Social Media Platforms Used for Online Advertising - Arc J. Datario; Rubenson M.Magraci; Altea M. Esquillo; Nicko A. Mganye; Glenda P. Binay (MultiTech Publisher, 2019)
This research study aims to investigate customer perceptions and experiences regarding affiliate sellers in social media. With the increasing prevalence of social media platforms as influential marketing channels, understanding how customers perceive and engage with affiliate sellers is crucial for both marketers and influencers.The study employs an online survey method to collect data from fifty five (55) random online shoppers as a diverse sample of social media users. The survey questionnaire comprises structured questions designed to assess customer perceptions and experiences with affiliate sellers, including their trust levels, perceived authenticity, purchase intentions, and satisfaction with recommended products. Additionally, demographic information is collected to analyze any potential variations in customer perceptions based on factors such as age, gender, and social media usage patterns.By understanding customer perceptions and experiences on affiliate sellers, marketers can enhance their understanding of consumer behavior in the context of social media marketing and optimize their affiliate marketing strategies accordingly. These insights can help marketers improve the effectiveness of their campaigns, build stronger relationships with customers, and drive higher levels of customer engagement and satisfaction.In conclusion, this quantitative research study provides valuable insights into customer perceptions and experiences regarding affiliate sellers in social media. The findings offer practical implications for marketers and influencers seeking to maximize the impact of their affiliate marketing efforts in the ever-evolving landscape of social media platforms Keywords: customers perception, affiliate sellers performance, increased sales to the market, exploring customers experiences.